k/4+6=-2

3 answers

To solve the equation k/4 + 6 = -2, we need to isolate the variable k on one side of the equation.

Subtract 6 from both sides of the equation:
k/4 = -2 - 6
k/4 = -8

To remove the fraction, multiply both sides of the equation by 4:
4(k/4) = 4(-8)
k = -32

Therefore, the solution to the equation k/4 + 6 = -2 is k = -32.
2/3n-6=-8
To solve the equation (2/3)n - 6 = -8, we need to isolate the variable n on one side of the equation.

Step 1: Add 6 to both sides of the equation:
(2/3)n - 6 + 6 = -8 + 6
(2/3)n = -2

Step 2: To remove the fraction, multiply both sides of the equation by 3/2 (the reciprocal of 2/3):
(3/2)(2/3)n = (-2)(3/2)
n = -3

Therefore, the solution to the equation (2/3)n - 6 = -8 is n = -3.